A holographic transparent medium electrochromic color resin composition and a method for preparing the same

CN122978795APending Publication Date: 2026-10-27SHANTOU JIAXIN PACKING MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611383379.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种透明介质电化铝色层树脂组合物及其制备方法,解决现有电化铝色层或透明介质相关体系在色层树脂设计、核壳粒子分散和连续化成膜过程中,高硬度、高耐磨与高透明、低雾度、均一透明外观之间难以兼顾,以及核壳粒子稳定分散和成膜均一性仍有待提升的问题

Benefits of technology

1.本发明通过将硅烷官能化丙烯酸共聚树脂与二氧化硅-硅烷官能化丙烯酸共聚树脂核壳中间体复合,引入核壳结构和界面硅氧键合特征,在保持高透明和低雾度的同时增强色层致密性,从而使色层兼具高硬度、高耐磨与均一透明外观,相较于单一树脂体系更易实现透明外观与耐久性的统一;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978795A_ABST
    Figure CN122978795A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of electrochemical aluminum resin materials, and provides a transparent medium electrochemical aluminum color layer resin composition and a preparation method thereof. Through the synergistic design of a silane functionalized acrylic copolymer resin, a silica-silane functionalized acrylic copolymer resin core-shell intermediate, a hydroxyl-containing polyurethane resin and a crosslinking agent, the component proportion, the core-shell interface bonding state and the mixing order are optimized, which is conducive to taking into account the high hardness, high wear resistance, high light transmittance, low haze and uniform transparent appearance of the color layer, and maintaining good stable dispersibility and film uniformity, and is suitable for the preparation of transparent medium electrochemical aluminum color layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electroplated aluminum functional coating resin technology, specifically to a holographic transparent dielectric electroplated aluminum color layer resin composition and its preparation method. Background Technology

[0002] In the application of transparent dielectric electroplated aluminum color layers, it is necessary not only to maintain high light transmittance and low haze, but also to ensure the uniformity of the final transparent appearance. Simultaneously, the color layer resin composition must maintain stable film formation during coating, drying, and transfer, and work synergistically with the related structures of the transparent medium. For such systems, pursuing only high hardness and high wear resistance often adversely affects high transparency, low haze, and transparent appearance; conversely, pursuing only high transparency and low viscosity may weaken the stable dispersion of core-shell particles, film uniformity, and wide processing window. Existing electroplated aluminum and transparent medium technologies all indicate that color layer performance, transparent medium processing, and adaptability to continuous processing require comprehensive design. Therefore, establishing a systematic resin composition scheme around the above indicators is of great significance.

[0003] Current research primarily focuses on optimizing the color layer of electroplated aluminum or the transparent medium carrier from a single perspective. For example, Chinese patent application CN1944552A discloses a colorant for electroplated aluminum coatings and its preparation method. The key technology lies in constructing a colorant system using polyurethane resin and resin modifiers to improve stability, hot stamping applicability, and heat resistance. However, it mainly focuses on the colorant itself, with relatively limited consideration for the system coordination of high transparency, low haze, and high wear resistance in transparent medium color layer scenarios. Similarly, Chinese patent application CN104029512A discloses a high-refractive-index transparent holographic film production process, emphasizing information layer carrying, medium layer evaporation, and transparent holographic imaging. However, this type of technology still faces challenges such as difficulty in controlling the uniformity of the transparent medium layer, increased interface interference, and the difficulty in balancing transparency and imaging performance. Therefore, existing technologies still have room for further improvement in terms of stable dispersion of core-shell particles, film uniformity, and the uniformity of the final transparent appearance. Summary of the Invention

[0004] The purpose of this invention is to provide a transparent dielectric electroplated aluminum color layer resin composition and its preparation method, which solves the problems of existing electroplated aluminum color layer or transparent dielectric related systems in the process of color layer resin design, core-shell particle dispersion and continuous film formation, where it is difficult to achieve both high hardness and high wear resistance with high transparency, low haze and uniform transparent appearance, as well as the need to improve the stable dispersion of core-shell particles and the uniformity of film formation.

[0005] This invention achieves a better balance of high hardness, high wear resistance, high transparency, low haze, stable dispersion, and film uniformity within the same system by synergistically configuring the transparent film-forming ability of silane-functionalized acrylic copolymer resin, the core-shell reinforcing effect of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, the film-forming regulating ability of hydroxyl-containing polyurethane resin, and the network curing ability of crosslinking agent.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a transparent dielectric electroplated aluminum color layer resin composition, comprising 100 parts by weight of each component in the color layer resin composition, including: 5.0–20.0 parts by weight of silane-functionalized acrylic copolymer resin, 0.5–6.0 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 1.0–10.0 parts by weight of hydroxyl-containing polyurethane resin, and 0.7–16.0 parts by weight of non-volatile components of the crosslinking agent stock solution, including 0.2–4 0.0 parts by weight of the crosslinking agent component containing isocyanate groups and 0.5 to 12.0 parts by weight of non-volatile components other than the crosslinking agent component containing isocyanate groups, and the balance solvent; the balance solvent includes the volatile solvents carried in the silane-functionalized acrylic copolymer resin solution, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, the hydroxyl-containing polyurethane resin solution and the crosslinking agent stock solution, and additional solvents, and the non-volatile components of the crosslinking agent stock solution are included in the non-volatile components of the color layer resin composition.

[0007] The silane-functionalized acrylic copolymer resin, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and the hydroxyl-containing polyurethane resin are all based on solid mass. The non-volatile components of the crosslinking agent stock solution are based on the residual mass after drying at 105°C for 1 hour. The effective isocyanate group content of the isocyanate-containing crosslinking agent component is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The isocyanate-containing crosslinking agent component is selected from one or both of hexamethylene diisocyanate trimer and isophorone diisocyanate. The solvent is selected from acetone, butanone, ethyl acetate, n-propyl acetate, and n-ethyl acetate. One or more of butyl acrylate; the silane-functionalized acrylic copolymer resin is obtained by reacting an acrylic copolymer resin composed of methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and acrylic acid with 3-glycidyloxypropyltrimethoxysilane; the core of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate is silica, the shell is the silane-functionalized acrylic copolymer resin, and the core and shell have an interfacial bonding state with silicon-oxygen bonding characteristics; the hydroxyl-containing polyurethane resin is obtained by reacting raw materials including isophorone diisocyanate, polytetramethylene ether glycol and 1,4-butanediol.

[0008] The non-volatile content mentioned in this article refers to the percentage of the residual mass of the sample after drying at 105°C for 1 hour relative to the initial mass of the sample; the transparent appearance mentioned in this article is characterized by total transmittance and haze. The molar ratio of isocyanate groups provided by the crosslinking agent to hydroxyl groups provided by the resin is calculated based on the effective isocyanate group content of the crosslinking agent stock solution and the hydroxyl value of each resin.

[0009] Furthermore, the acrylic copolymer resin is prepared according to the following steps: A1. A monomer mixture is prepared based on a total monomer mass of 100 parts by weight, wherein the monomer mixture consists of 35-55 parts by weight of methyl methacrylate, 25-45 parts by weight of butyl acrylate, 12-18 parts by weight of hydroxyethyl methacrylate and 3-8 parts by weight of acrylic acid, and the total is 100 parts by weight. A2, add 120-260 parts by weight of n-butyl acetate to the reaction vessel, and heat to 100-120°C under nitrogen protection; A3, dissolve 0.3 to 1.5 parts by weight of 2,2'-azobisisobutyronitrile in 10 to 40 parts by weight of n-butyl acetate to obtain an initiator solution, and simultaneously add the monomer mixture and the initiator solution dropwise over 2.0 to 4.0 hours at 100 to 120°C; A4. After the addition is complete, keep the temperature at 100-120℃ for 2.0-3.0h, then add 0.05-0.50 parts by weight of 2,2'-azobisisobutyronitrile. The added 2,2'-azobisisobutyronitrile is pre-dissolved in 1-10 parts by weight of n-butyl acetate to form a replenishing solution before being added to the reaction system, and the temperature is kept high for another 0.5-1.5h. A5, cooled to 40-60℃, and according to the solid content test results, partially removed n-butyl acetate under reduced pressure at 40-60℃ and an absolute pressure of 0.04-0.06MPa, or n-butyl acetate was added to adjust the solid content, to obtain the acrylic copolymer resin solution with a solid content of 25.0-43.0wt%. A6, the resulting acrylic copolymer resin has an acid value of 15-35 mg KOH / g and a hydroxyl value of 50-77 mg KOH / g based on resin solids.

[0010] Furthermore, the silane-functionalized acrylic copolymer resin is prepared according to the following steps: B1, take an acrylic copolymer resin solution, and add 1 to 15 parts by weight of 3-glycidyloxypropyltrimethoxysilane to 100 parts by weight of the acrylic copolymer resin solids. B2, under nitrogen protection, reacts at 60–90°C for 1.0–4.0 h; B3, the acid value of the silane-functionalized acrylic copolymer resin obtained after the reaction is 5-35 mg KOH / g based on resin solids; B4 is cooled to 40–60°C. Based on the solid content test results, some of the n-butyl acetate is removed under reduced pressure at 40–60°C and an absolute pressure of 0.04–0.06 MPa, or n-butyl acetate is added to adjust the solid content, to obtain the silane-functionalized acrylic copolymer resin solution with a solid content of 25.0–50.0 wt%.

[0011] Furthermore, the silica-silane-functionalized acrylic copolymer core-shell intermediate is prepared according to the following steps: C1, add 10 to 60 parts by weight of silica to 100 to 400 parts by weight of ethanol to form a silica dispersion system without visible agglomerates; C2, add 5-80 parts by weight of deionized water and 0.1-10 parts by weight of glacial acetic acid at 20-40℃ to make the apparent pH of the system 4.0-6.0 and maintain it for 0.5-2.0h; C3. Add a silane-functionalized acrylic copolymer resin solution to the system obtained in step C2, with 10 to 120 parts by weight of the silane-functionalized acrylic copolymer resin solids, and react at 40 to 70°C for 1.0 to 4.0 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. C4, at 40–60°C and an absolute pressure of 0.02–0.08 MPa, ethanol and water are removed from the core-shell intermediate dispersion system obtained in step C3 by vacuum distillation or rotary evaporation, and one or more of acetone, butanone, ethyl acetate, n-propyl acetate and n-butyl acetate are added simultaneously to complete solvent replacement, thereby obtaining the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion; C5, wherein the silica content in the core-shell intermediate is 10-60 wt% based on the total dry basis of the core-shell intermediate, the core particle size is 10-60 nm, and the shell thickness is 3-15 nm.

[0012] Furthermore, the hydroxyl-containing polyurethane resin is prepared according to the following steps: D1, based on 100 parts by weight of polytetramethylene ether glycol, provides polytetramethylene ether glycol with a number average molecular weight of 1800-2200 g / mol and a hydroxyl value of 50-65 mg KOH / g, 0.05-0.50 parts by weight of 1,4-butanediol, 10.0-13.0 parts by weight of isophorone diisocyanate and 70-255 parts by weight of n-butyl acetate; D2 is prepared with the molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol being 1.02 to 1.05. D3, under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol are reacted at 70-90°C for 1.0-3.0 h to obtain isocyanate-terminated prepolymer; D4, add 1,4-butanediol, and based on the residual isocyanate group content at the end of step D3, make the molar ratio of the hydroxyl groups provided by 1,4-butanediol to the residual isocyanate groups 1.05 to 1.30, and react at 60 to 80°C for 1.0 to 4.0 h. D5, cooled to 40-60°C, and butyl acetate was added to adjust the solid content according to the solid content test results, to obtain the hydroxyl-containing polyurethane resin solution with a solid content of 30.0-60.0 wt%.

[0013] Further, the solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer is 1:40 to 6:5; the crosslinking agent component containing isocyanate groups is hexamethylene diisocyanate trimer, and the amount of the crosslinking agent component containing isocyanate groups is 0.5 to 3.0 parts by weight; the solvent is composed of ethyl acetate and n-butyl acetate, or composed of ethyl acetate, n-butyl acetate, and one or more selected from acetone, butanone, and n-propyl acetate, and the sum of the amounts of each solvent component relative to the total amount of the color layer resin composition is the balance solvent in the color layer resin composition; the molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer and the hydroxyl-containing polyurethane resin is 0.80 to 1.20.

[0014] As a concept of this invention, a composite design is employed, consisting of silane-functionalized acrylic copolymer resin, a silica-silane-functionalized acrylic copolymer resin core-shell intermediate, a hydroxyl-containing polyurethane resin, and a crosslinking agent. This design primarily enhances the high hardness, high wear resistance, high transparency, low haze, and uniform transparent appearance of the transparent dielectric electroplated aluminum color layer. The silane-functionalized acrylic copolymer resin facilitates the formation of a transparent and stable color layer base. The silica-silane-functionalized acrylic copolymer resin core-shell intermediate utilizes the core-shell structure and interfacial silicon-oxygen bonding characteristics to improve the system's stable dispersion and film-forming uniformity. The hydroxyl-containing polyurethane resin helps to balance film formation and a wide processing window. The crosslinking agent further enhances the network stability after curing. Therefore, the system effectively balances stable dispersion of core-shell particles, uniform transparent appearance, and comprehensive color layer performance.

[0015] This invention also discloses a method for preparing a transparent dielectric electroplated aluminum color layer resin composition, comprising the following steps: S1 provides an acrylic copolymer resin solution; S2, react the acrylic copolymer resin solution provided in step S1 with 3-glycidyloxypropyltrimethoxysilane to obtain a silane-functionalized acrylic copolymer resin solution. S3 provides a silica-silane-functionalized acrylic copolymer core-shell intermediate dispersion; S4 provides a hydroxyl-containing polyurethane resin solution; S5, at 15-35°C, the silane-functionalized acrylic copolymer resin solution provided in step S2, the hydroxyl-containing polyurethane resin solution provided in step S4, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion provided in step S3, and the solvent are mixed and stirred in sequence, and then a crosslinking agent is added to obtain the transparent dielectric electroplated aluminum color layer resin composition.

[0016] Furthermore, the crosslinking agent in step S5 is added 0.1 to 2.0 h before coating; the color layer resin composition obtained in step S5 is filtered through 5 to 20 µm before coating, and the non-volatile content of the color layer resin composition is 20.0 to 40.0 wt%.

[0017] Furthermore, the color layer resin composition obtained in step S5 is further coated using one of gravure coating, microgravure coating, or slot coating; the resulting dry film thickness is 0.5–5.0 µm; the drying temperature is 60–130 °C, and the drying time is 10–120 s.

[0018] Furthermore, the preparation processes of the acrylic copolymer resin solution provided in step S1, the silane-functionalized acrylic copolymer resin solution provided in step S2, and the hydroxyl-containing polyurethane resin solution provided in step S4 are all carried out under nitrogen protection; in step S5, after adding the silane-functionalized acrylic copolymer resin solution and the hydroxyl-containing polyurethane resin solution, they are stirred for 10-20 min respectively, after adding the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, they are stirred for 10-20 min, after adding the solvent, they are stirred for 20-40 min, and after adding the crosslinking agent, they are stirred for 10-30 min.

[0019] Furthermore, the solvents carried in the silane-functionalized acrylic copolymer resin solution, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, and the hydroxyl-containing polyurethane resin solution, as well as the volatile solvents carried in the crosslinking agent stock solution, are all included in the balance solvent. All non-volatile components in the crosslinking agent stock solution are included in the non-volatile components, and the non-volatile component content is calculated as a percentage of the actual dried residual mass to the actual total mass of the color layer resin composition.

[0020] Furthermore, the 2,2'-azobisisobutyronitrile added in step A4 is pre-dissolved in 1 to 10 parts by weight of n-butyl acetate to form an addition solution before being added to the reaction system.

[0021] Furthermore, in step A5, based on the solid content test results, some n-butyl acetate is removed under reduced pressure at 40–60°C and an absolute pressure of 0.04–0.06 MPa, or n-butyl acetate is added to adjust the solid content of the acrylic copolymer resin solution. In step D5, n-butyl acetate is added to adjust the solid content of the hydroxyl-containing polyurethane resin solution.

[0022] Further, after cooling to 40-60°C in step B4, based on the solid content test results, some n-butyl acetate is removed under reduced pressure at 40-60°C and an absolute pressure of 0.04-0.06 MPa, or n-butyl acetate is added to adjust the solid content, to obtain a silane-functionalized acrylic copolymer resin solution with a solid content of 25.0-50.0 wt%.

[0023] Furthermore, in step C1, the silica is dispersed in ethanol by ultrasonic dispersion at 20-30°C to form a uniform dispersion system. The ultrasonic power is 300-500W, the frequency is 20-40kHz, and the time is 30-60min.

[0024] Further, in step C2, deionized water is added first, followed by glacial acetic acid, to make the apparent pH of the system 4.0–6.0, and this is maintained for 0.5–2.0 h. The apparent pH is measured at 20–40 °C using a composite glass electrode calibrated with pH 4.00 and pH 6.86 buffer solutions, and the recorded value is the apparent pH of the system after adding acid and stirring evenly.

[0025] Furthermore, in step C4, ethanol and water are removed by vacuum distillation or rotary evaporation at 40–60°C and an absolute pressure of 0.02–0.08 MPa, and one or more of ethyl acetate, n-butyl acetate, acetone, butanone, and n-propyl acetate are added simultaneously to complete solvent replacement.

[0026] Furthermore, the silica-silane functionalized acrylic copolymer resin core-shell intermediate obtained after step C4 is an organic solvent-based dispersion with a residual ethanol content of no more than 1.0 wt% and a residual water content of no more than 0.5 wt%. The residual ethanol content is determined by headspace gas chromatography, and the residual water content is determined by Karl Fischer method. The test sample is the core-shell intermediate dispersion obtained after step C4.

[0027] Furthermore, in step D4, 1,4-butanediol is added, and based on the residual isocyanate group content at the end of step D3, the molar ratio of the hydroxyl groups provided by 1,4-butanediol to the residual isocyanate groups is 1.05 to 1.30.

[0028] Further, in step S5, each component is added sequentially by mechanical stirring. After adding the silane-functionalized acrylic copolymer resin solution and the hydroxyl-containing polyurethane resin solution, the mixture is stirred for 10-20 minutes. After adding the core-shell intermediate dispersion, the mixture is stirred for 10-20 minutes. After adding the solvent, the mixture is stirred for 20-40 minutes. Then, the crosslinking agent is added and the mixture is stirred for 10-30 minutes to obtain a color layer resin composition without visible layering and sedimentation.

[0029] Furthermore, the particle size of the core and the shell thickness were determined using transmission electron microscopy. The test sample was obtained by diluting the core-shell intermediate dispersion, dropping it onto a copper grid, and drying it. Each sample contained no fewer than 100 particles. The particle size of the core was the numerical mean of the diameter of the silica core, and the shell thickness was half the difference between the outer diameter of the near-spherical core-shell particle and the core diameter. The interfacial silicon-oxygen bonding state between the core and the shell was characterized by comparison using infrared spectroscopy or X-ray photoelectron spectroscopy.

[0030] As another aspect of this invention, the present invention employs a method of providing acrylic copolymer resin, silane-functionalized acrylic copolymer resin solution, silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, and hydroxyl-containing polyurethane resin solution in steps, and mixing them in a predetermined order at 15–35°C before adding a crosslinking agent. This method is mainly used to enhance the stable dispersion, film uniformity, and transparent appearance uniformity of the transparent dielectric electroplated aluminum color layer. By introducing the core-shell intermediate dispersion and resin solution in steps, the risk of local instability during the mixing process can be reduced. The crosslinking agent is added later and combined with the control of filtration, coating, and drying conditions, which helps to balance the requirements of 20.0–40.0 wt% non-volatile content, application viscosity, wide processing window, and transparent appearance, making the resulting color layer resin composition more suitable for continuous preparation and application.

[0031] The focus of silane-functionalized acrylic copolymer resins is to provide a transparent film-forming basis and reactive sites, directly contributing to high transparency, low haze, and a transparent appearance. The focus of silica-silane-functionalized acrylic copolymer resin core-shell intermediates is to enhance high hardness, high wear resistance, and stable dispersion by leveraging the rigidity of the silica core and the compatibility of the shell. The former helps maintain continuous and uniform color layers and reduces the risk of haze increase, while the latter enhances structural stability and inhibits particle aggregation through its core-shell structure and interfacial silicon-oxygen bonding characteristics. When both coexist, they can maintain high transparency, low haze, and uniform transparent appearance while improving film uniformity and overall color layer strength, achieving a better balance between transparent appearance and durability requirements within the same system.

[0032] Beneficial technical effects 1. This invention introduces a core-shell structure and interfacial silicon-oxygen bonding characteristics by compositing silane-functionalized acrylic copolymer resin with a silica-silane-functionalized acrylic copolymer resin core-shell intermediate. This enhances the density of the color layer while maintaining high transparency and low haze, thus giving the color layer both high hardness, high wear resistance and uniform transparent appearance. Compared with a single resin system, it is easier to achieve a balance between transparent appearance and durability. 2. By introducing a hydroxyl-containing polyurethane resin and combining it with a crosslinking agent, this invention takes into account both the reactivity of the resin composition and its film-forming ability. It can maintain a low viscosity and a wide processing window under high solid content conditions, thereby reducing the risk of instability during mixing, coating and drying, and improving the stable dispersion of core-shell particles and the uniformity of film formation. 3. By limiting the type of crosslinking agent, the molar ratio of isocyanate groups to hydroxyl groups, and the mixing order, the present invention makes the curing network establishment process more controllable, which helps to avoid excessive crosslinking or dispersion imbalance in the local color layer, thereby improving the uniformity of transparent appearance and improving the construction stability under continuous processing conditions. 4. This invention, through the synergistic design of the content of core-shell intermediates, the particle size of the core, the thickness of the shell, and the solvent system, matches the inorganic reinforcement effect with the requirements of the transparent medium. While ensuring high light transmittance and low haze, it also takes into account the adaptability of construction and the stability of subsequent use. Compared with the solution that focuses on single coloring or single transparent medium treatment, it is more in line with the application requirements of transparent medium electroplated aluminum color layer. Attached Figure Description

[0033] Figure 1 The graph shows the effect of the amount of silica-silane-functionalized acrylic copolymer core-shell intermediate on light transmittance and abrasion resistance weight loss. Figure 2 The graph shows the effect of the molar ratio of isocyanate groups to hydroxyl groups on light transmittance and abrasion weight loss. Figure 3 The graph shows the effect of silica core particle size on light transmittance and abrasion resistance weight loss. Figure 4 The figure shows the effect of the shell thickness of the core-shell intermediate on light transmittance and wear resistance weight loss. Figure 5 The graph shows the effect of drying temperature on light transmittance and abrasion-resistant weight loss. Figure 6 The ATR-FTIR normalized spectra of Example 1, Comparative Example 1, and Comparative Example 2 are shown below. Figure 7 This is an example of XPS Si 2p peak fitting from Example 1; Figure 8 The above is a statistical chart of the Si–O–Si / Si–OH peak area ratio for Example 1, Comparative Example 1, and Comparative Example 2. Figure 9The TEM particle size difference distribution curves for Example 1, Comparative Example 2, and Comparative Example 4 are shown. Figure 10 The graph shows the gel content statistics for Example 1, Comparative Example 6, and Comparative Example 7. Figure 11 The swelling rate statistics are shown for Example 1, Comparative Example 6, and Comparative Example 7. Figure 12 The graph shows the MEK abrasion resistance statistics for Example 1, Comparative Example 6, and Comparative Example 7. Figure 13 The chart shows the wear resistance weight loss statistics for Example 1, Comparative Example 6, and Comparative Example 7. Figure 14 Viscosity-shear rate rheological curves for Example 1 and Comparative Example 7; Figure 15 The static stability settlement height curves for Example 1 and Comparative Example 7 are shown. Figure 16 The transmittance statistics are shown for Example 1, Comparative Example 7, and Comparative Example 8. Figure 17 These are macroscopic optical photographs comparing the final product of Example 1 and the final product of Comparative Example 2; wherein, Figure 17 Figure a in the image is a macroscopic optical photograph of the final product of Example 1; Figure 17 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 2; Figure 18 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 2; where, Figure 18 Figure a in the image is a low-magnification SEM image of the final product of Example 1; Figure 18 Figure b in the image is a low-magnification SEM image of the final product of Comparative Example 2; Figure 18 Figure c in the image is a medium-magnification SEM image of the final product of Example 1; Figure 18 Image d in the figure is a medium-magnification SEM image of the final product of Comparative Example 2; Figure 18 Image e in the figure is a high-magnification SEM image of the final product of Example 1; Figure 18 Figure f in the figure is a high-magnification SEM image of the final product of Comparative Example 2; Figure 19 The images show a comparison of the TEM structures of the final product of Example 1 and the final product of Comparative Example 2; where, Figure 19 Figure a in the image is a bright-field TEM image of the final product of Example 1; Figure 19 Image b in the figure is a bright-field TEM image of the final product of Comparative Example 2; Figure 19 Figure c in the figure is an HRTEM image of the final product of Example 1; Figure 19 The d-image in the figure is the HRTEM image of the final product of Comparative Example 2. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0035] Example 1 I. Preparation of Acrylic Copolymer Resin: A monomer mixture was prepared based on a total monomer mass of 100 parts by weight. The monomer mixture consisted of 45 parts by weight of methyl methacrylate, 35 parts by weight of butyl acrylate, 12 parts by weight of hydroxyethyl methacrylate, and 8 parts by weight of acrylic acid. 190 parts by weight of n-butyl acetate was added to a reaction vessel, and the temperature was raised to 110°C under nitrogen protection. 0.9 parts by weight of 2,2'-azobisisobutyronitrile was dissolved in 25 parts by weight of n-butyl acetate to obtain an initiator solution. The monomer mixture and initiator solution were simultaneously added dropwise over 3.0 hours at 110°C. After the addition was completed, the temperature was maintained at 110°C for 2.5 hours. Then, 0.28 parts by weight of 2,2'-azobisisobutyronitrile, pre-dissolved in 5.0 parts by weight of n-butyl acetate to form a replenishing solution, was added, and the temperature was maintained for another 1.0 hour. The solution was cooled to 50°C, and partially butyl acetate was removed under reduced pressure at 50°C and 0.05 MPa. The solid content was then adjusted with butyl acetate to obtain an acrylic copolymer resin solution with a solid content of 34.0 wt%. The resulting acrylic copolymer resin had an acid value of 25 mg KOH / g and a hydroxyl value of 50 mg KOH / g. II. Preparation of silane-functionalized acrylic copolymer resin: Take the above acrylic copolymer resin solution, and add 8 parts by weight of 3-glycidyloxypropyltrimethoxysilane to 100 parts by weight of acrylic copolymer resin solids. React at 75°C for 2.5 h under nitrogen protection. The acid value of the silane-functionalized acrylic copolymer resin obtained after the reaction is 20 mg KOH / g. Cool to 50°C, and remove part of the n-butyl acetate under reduced pressure at 50°C and an absolute pressure of 0.05 MPa. Adjust the solid content with n-butyl acetate to obtain a silane-functionalized acrylic copolymer resin solution with a solid content of 37.5 wt%. III. Preparation of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate: 35 parts by weight of silica were added to 250 parts by weight of ethanol. The silica was uniformly dispersed by ultrasonication at 25°C with a power of 400 W, a frequency of 30 kHz, and a time of 45 min. At 30°C, 42 parts by weight of deionized water were added first, followed by 5.0 parts by weight of glacial acetic acid to adjust the apparent pH of the system to 5.0, and this was maintained for 1.2 h. A silane-functionalized acrylic copolymer resin solution was added to the above system, with 65 parts by weight based on the solid content of the silane-functionalized acrylic copolymer resin. The reaction was carried out at 55°C for 2.5 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. Ethanol and water were removed by rotary evaporation at 50°C and 0.05 MPa absolute pressure, with simultaneous addition of ethyl acetate and n-butyl acetate to complete solvent replacement, yielding a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion with a solid content of 30.0 wt%, residual ethanol content of 0.6 wt%, and residual water content of 0.3 wt%. In this embodiment, the silica content in the core-shell intermediate is 35 wt% on a dry basis, the core particle size is 35 nm, the shell thickness is 9 nm, and the core and shell exhibit an interfacial bonding state with silicon-oxygen bonding characteristics. IV. Preparation of Hydroxyl-Containing Polyurethane Resin: 100 parts by weight of polytetramethylene ether glycol, 0.18 parts by weight of 1,4-butanediol, 11.5 parts by weight of isophorone diisocyanate, and 136.5 parts by weight of n-butyl acetate were provided, with a number average molecular weight of 2000 g / mol and a hydroxyl value of 56 mg KOH / g. The mixture was formulated with a molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol of 1.035. Under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol were reacted at 80°C for 2.0 h to obtain an isocyanate-terminated prepolymer. 1,4-Butanediol was added to make the molar ratio of hydroxyl groups provided by 1,4-butanediol to residual isocyanate groups in the isocyanate-terminated prepolymer 1.10, and the mixture was reacted at 70°C for 2.5 h. The mixture was cooled to 50°C and adjusted with n-butyl acetate to obtain a hydroxyl-containing polyurethane resin solution with a solid content of 45.0 wt%. V. Preparation of the transparent dielectric electroplated aluminum color layer resin composition: Based on 100 parts by weight of the color layer resin composition in this embodiment, at 25°C, a silane-functionalized acrylic copolymer resin solution, a hydroxyl-containing polyurethane resin solution, and a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion were added sequentially. After each component was added, the mixture was stirred for 15 minutes, followed by the addition of the solvent and stirring for 30 minutes. One hour before coating, the crosslinking agent hexamethylene diisocyanate trimer was added and stirred for 20 minutes until no visible layering or sedimentation was observed in the system.

[0036] The color layer resin composition of this embodiment comprises, by weight, the following components: 12.5 parts by weight of silane-functionalized acrylic copolymer resin, 3.0 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 5.5 parts by weight of hydroxyl-containing polyurethane resin, 2.0 parts by weight of isocyanate-containing crosslinking agent component containing hexamethylene diisocyanate trimer, 7.0 parts by weight of non-volatile components in the crosslinking agent stock solution other than the isocyanate-containing crosslinking agent component, and 70.0 parts by weight of solvent. The silane-functionalized acrylic copolymer resin, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and the hydroxyl-containing polyurethane resin of this embodiment are all based on solid mass. The effective isocyanate group content of the isocyanate-containing crosslinking agent component in this embodiment is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The non-volatile components of the crosslinking agent stock solution are included in the non-volatile components of this embodiment. In this embodiment, the solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer resin is 0.24. The solvent in this embodiment consists of ethyl acetate and n-butyl acetate, including the volatile solvent carried in the silane-functionalized acrylic copolymer resin solution, the core-shell intermediate dispersion, the hydroxyl-containing polyurethane resin solution, and the crosslinking agent stock solution, as well as additionally added solvent. The molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin in this embodiment is 1.00.

[0037] The color layer resin composition of this embodiment was filtered through a 12µm filter and had a non-volatile content of 30.0wt%. The color layer resin composition was coated onto the substrate using a gravure coating method, with a dry film thickness of 2.8µm, a drying temperature of 95°C, and a drying time of 65s.

[0038] Example 2 I. Preparation of Acrylic Copolymer Resin: A monomer mixture was prepared based on a total monomer mass of 100 parts by weight. In this embodiment, the monomer mixture consisted of 38 parts by weight of methyl methacrylate, 42 parts by weight of butyl acrylate, 14 parts by weight of hydroxyethyl methacrylate, and 6 parts by weight of acrylic acid. 145 parts by weight of n-butyl acetate was added to the reaction vessel, and the temperature was raised to 105°C under nitrogen protection. 0.5 parts by weight of 2,2'-azobisisobutyronitrile was dissolved in 15 parts by weight of n-butyl acetate to obtain an initiator solution. The monomer mixture and initiator solution were simultaneously added dropwise over 2.5 hours at 105°C. After the addition was completed, the temperature was maintained at 105°C for 2.2 hours. Then, 0.15 parts by weight of 2,2'-azobisisobutyronitrile was pre-dissolved in 3.0 parts by weight of n-butyl acetate to form a replenishing solution, and the temperature was maintained for another 0.8 hours. The solution was cooled to 45°C, and butyl acetate was added to adjust the solid content, yielding an acrylic copolymer resin solution with a solid content of 28.5 wt%. The resulting acrylic copolymer resin had an acid value of 18 mg KOH / g and a hydroxyl value of 58 mg KOH / g. II. Preparation of silane-functionalized acrylic copolymer resin: Take the above acrylic copolymer resin solution, and add 4 parts by weight of 3-glycidyloxypropyltrimethoxysilane to 100 parts by weight of the acrylic copolymer resin solids. React at 65°C for 1.8 h under nitrogen protection. The acid value of the obtained silane-functionalized acrylic copolymer resin after the reaction is 12 mg KOH / g. Cool to 45°C, and remove part of the n-butyl acetate under reduced pressure at 45°C and an absolute pressure of 0.04 MPa. Adjust the solid content with n-butyl acetate to obtain a silane-functionalized acrylic copolymer resin solution with a solid content of 30.0 wt%. III. Preparation of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate: 20 parts by weight of silica were added to 150 parts by weight of ethanol. The silica was uniformly dispersed by ultrasonication at 25°C with a power of 350 W, a frequency of 25 kHz, and a time of 40 min. At 25°C, 22 parts by weight of deionized water were added first, followed by 2.0 parts by weight of glacial acetic acid to adjust the apparent pH of the system to 5.4, and this pH was maintained for 0.8 h. A silane-functionalized acrylic copolymer resin solution was then added to the above system, with 38 parts by weight based on the solid content of the silane-functionalized acrylic copolymer resin. The reaction was carried out at 48°C for 1.8 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. Ethanol and water were removed by rotary evaporation at 45°C and 0.04 MPa absolute pressure, with simultaneous addition of ethyl acetate and acetone to complete solvent replacement, yielding a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion with a solid content of 26.0 wt%, residual ethanol content of 0.4 wt%, and residual water content of 0.2 wt%. In this embodiment, the silica content in the core-shell intermediate was 34.5 wt% on a dry basis, the core particle size was 22 nm, the shell thickness was 6 nm, and the core and shell exhibited an interfacial bonding state with silicon-oxygen bonding characteristics. IV. Preparation of Hydroxyl-Containing Polyurethane Resin: 100 parts by weight of polytetramethylene ether glycol, 0.13 parts by weight of 1,4-butanediol, 11.4 parts by weight of isophorone diisocyanate, and 198.3 parts by weight of n-butyl acetate were provided, with a number average molecular weight of 2000 g / mol and a hydroxyl value of 56 mg KOH / g. The mixture was prepared by adjusting the molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol to 1.025. Under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol were reacted at 75°C for 1.5 h to obtain an isocyanate-terminated prepolymer. 1,4-Butanediol was added to achieve a molar ratio of hydroxyl groups provided by 1,4-butanediol to residual isocyanate groups in the isocyanate-terminated prepolymer of 1.05, and the mixture was reacted at 65°C for 1.8 h. The mixture was cooled to 45°C and adjusted with n-butyl acetate to obtain a hydroxyl-containing polyurethane resin solution with a solid content of 36.0 wt%. V. Preparation of the transparent dielectric electroplated aluminum color layer resin composition: Based on 100 parts by weight of the color layer resin composition in this embodiment, at 20°C, a silane-functionalized acrylic copolymer resin solution, a hydroxyl-containing polyurethane resin solution, and a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion were added sequentially. After each component was added, the mixture was stirred for 12 minutes, followed by the addition of a solvent and stirring for 25 minutes. A crosslinking agent was added 0.5 hours before coating. In this embodiment, the crosslinking agent was a mixture of hexamethylene diisocyanate trimer and isophorone diisocyanate (mass ratio 7:3). The mixture was stirred for 15 minutes until no visible layering or sedimentation was observed.

[0039] The color layer resin composition of this embodiment comprises, by weight, the following components: 8.0 parts by weight of silane-functionalized acrylic copolymer resin, 1.5 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 3.0 parts by weight of hydroxyl-containing polyurethane resin, 1.0 part by weight of an isocyanate-containing crosslinking agent component composed of hexamethylene diisocyanate trimer and isophorone diisocyanate, 9.0 parts by weight of non-volatile components in the crosslinking agent stock solution other than the isocyanate-containing crosslinking agent component, and 77.5 parts by weight of solvent. The silane-functionalized acrylic copolymer resin, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and the hydroxyl-containing polyurethane resin of this embodiment are all based on solid mass. The effective isocyanate group content of the isocyanate-containing crosslinking agent component in this embodiment is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The non-volatile components of the crosslinking agent stock solution are included in the non-volatile components of this embodiment. In this embodiment, the solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer resin is 0.19. The solvent in this embodiment consists of ethyl acetate, n-butyl acetate, and acetone, including the volatile solvents carried in the silane-functionalized acrylic copolymer resin solution, the core-shell intermediate dispersion, the hydroxyl-containing polyurethane resin solution, and the crosslinking agent stock solution, as well as additionally added solvent. The molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin in this embodiment is 0.88.

[0040] The color layer resin composition of this embodiment was filtered through an 8µm filter, and the non-volatile content was 22.5wt%. The color layer resin composition was coated onto the substrate using a microgravure coating method, with a dry film thickness of 1.2µm, a drying temperature of 75°C, and a drying time of 35s.

[0041] Example 3 I. Preparation of Acrylic Copolymer Resin: A monomer mixture was prepared based on a total monomer mass of 100 parts by weight. In this embodiment, the monomer mixture consisted of 52 parts by weight of methyl methacrylate, 28 parts by weight of butyl acrylate, 15 parts by weight of hydroxyethyl methacrylate, and 5 parts by weight of acrylic acid. 235 parts by weight of n-butyl acetate was added to the reaction vessel, and the temperature was raised to 115°C under nitrogen protection. 1.3 parts by weight of 2,2'-azobisisobutyronitrile was dissolved in 35 parts by weight of n-butyl acetate to obtain an initiator solution. The monomer mixture and initiator solution were simultaneously added dropwise over 3.5 hours at 115°C. After the addition was completed, the temperature was maintained at 115°C for 2.8 hours. Then, 0.42 parts by weight of 2,2'-azobisisobutyronitrile was pre-dissolved in 7.0 parts by weight of n-butyl acetate to form a replenishing solution, which was then added, and the temperature was maintained for another 1.3 hours. The solution was cooled to 55°C, and partially butyl acetate was removed under reduced pressure at 55°C and 0.06 MPa. The solid content was then adjusted with butyl acetate to obtain an acrylic copolymer resin solution with a solid content of 40.5 wt%. The resulting acrylic copolymer resin had an acid value of 35 mg KOH / g and a hydroxyl value of 63 mg KOH / g. II. Preparation of silane-functionalized acrylic copolymer resin: Take the above acrylic copolymer resin solution, and add 13 parts by weight of 3-glycidyloxypropyltrimethoxysilane (based on 100 parts by weight of solid acrylic copolymer resin). React at 85°C for 3.5 h under nitrogen protection. The acid value of the resulting silane-functionalized acrylic copolymer resin is 30 mg KOH / g. Cool to 55°C, and remove part of the n-butyl acetate under reduced pressure at 55°C and 0.06 MPa. Adjust the solid content with n-butyl acetate to obtain a silane-functionalized acrylic copolymer resin solution with a solid content of 46.0 wt%. III. Preparation of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate: 52 parts by weight of silica were added to 360 parts by weight of ethanol. The silica was uniformly dispersed by ultrasonication at 28°C with a power of 480 W, a frequency of 38 kHz, and a time of 55 min. At 35°C, 68 parts by weight of deionized water were added first, followed by 8.5 parts by weight of glacial acetic acid, to adjust the apparent pH of the system to 4.5, and this was maintained for 1.8 h. A silane-functionalized acrylic copolymer resin solution was added to the above system, with 105 parts by weight based on the solid content of the silane-functionalized acrylic copolymer resin. The reaction was carried out at 65°C for 3.5 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. Ethanol and water were removed by vacuum distillation at 58°C and 0.07 MPa, with simultaneous addition of n-propyl acetate and n-butyl acetate to complete solvent replacement, yielding a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion with a solid content of 36.0 wt%, residual ethanol content of 0.8 wt%, and residual water content of 0.4 wt%. In this embodiment, the silica content in the core-shell intermediate was 33.1 wt% on a dry basis, the core particle size was 52 nm, the shell thickness was 13 nm, and the core and shell exhibited an interfacial bonding state with silicon-oxygen bonding characteristics. IV. Preparation of Hydroxyl-Containing Polyurethane Resin: 100 parts by weight of polytetramethylene ether glycol, 0.26 parts by weight of 1,4-butanediol, 11.65 parts by weight of isophorone diisocyanate, and 91.6 parts by weight of n-butyl acetate were provided, with a number average molecular weight of 2000 g / mol and a hydroxyl value of 56 mg KOH / g. The mixture was formulated with a molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol of 1.048. Under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol were reacted at 88°C for 2.8 h to obtain an isocyanate-terminated prepolymer. 1,4-Butanediol was added to make the molar ratio of hydroxyl groups provided by 1,4-butanediol to residual isocyanate groups in the isocyanate-terminated prepolymer 1.20, and the mixture was reacted at 78°C for 3.5 h. The mixture was cooled to 58°C and adjusted with n-butyl acetate to obtain a hydroxyl-containing polyurethane resin solution with a solid content of 55.0 wt%. V. Preparation of the transparent dielectric electroplated aluminum color layer resin composition: Based on 100 parts by weight of the color layer resin composition in this embodiment, at 30°C, a silane-functionalized acrylic copolymer resin solution, a hydroxyl-containing polyurethane resin solution, and a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion were added sequentially. After each component was added, the mixture was stirred for 18 minutes, followed by the addition of the solvent and stirring for 35 minutes. 1.6 hours before coating, the crosslinking agent hexamethylene diisocyanate trimer was added and stirred for 25 minutes until no visible layering or sedimentation was observed in the system.

[0042] The color layer resin composition of this embodiment comprises, by weight, the following components: 16.0 parts by weight of silane-functionalized acrylic copolymer resin, 4.5 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 7.5 parts by weight of hydroxyl-containing polyurethane resin, 3.0 parts by weight of isocyanate-containing crosslinking agent component containing hexamethylene diisocyanate trimer, 6.5 parts by weight of non-volatile components in the crosslinking agent stock solution other than the isocyanate-containing crosslinking agent component, and 62.5 parts by weight of solvent. The silane-functionalized acrylic copolymer resin, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and the hydroxyl-containing polyurethane resin of this embodiment are all based on solid mass. The effective isocyanate group content of the isocyanate-containing crosslinking agent component in this embodiment is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The non-volatile components of the crosslinking agent stock solution are included in the non-volatile components of this embodiment. In this embodiment, the solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer resin is 0.28. The solvent in this embodiment consists of ethyl acetate, n-propyl acetate, and n-butyl acetate, and includes volatile solvents carried in the silane-functionalized acrylic copolymer resin solution, the core-shell intermediate dispersion, the hydroxyl-containing polyurethane resin solution, and the crosslinking agent stock solution, as well as additionally added solvent. The molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin in this embodiment is 1.15.

[0043] The color layer resin composition of this embodiment was filtered through an 18µm filter, and the non-volatile content was 37.5wt%. The color layer resin composition was coated onto the substrate using a slot coating method, with a dry film thickness of 4.2µm, a drying temperature of 120°C, and a drying time of 95s.

[0044] Example 4 I. Preparation of Acrylic Copolymer Resin: A monomer mixture was prepared based on a total monomer mass of 100 parts by weight. In this embodiment, the monomer mixture consisted of 53 parts by weight of methyl methacrylate, 26 parts by weight of butyl acrylate, 18 parts by weight of hydroxyethyl methacrylate, and 3 parts by weight of acrylic acid. 250 parts by weight of n-butyl acetate was added to the reaction vessel, and the temperature was raised to 118°C under nitrogen protection. 1.45 parts by weight of 2,2'-azobisisobutyronitrile was dissolved in 38 parts by weight of n-butyl acetate to obtain an initiator solution. The monomer mixture and initiator solution were simultaneously added dropwise over 3.8 hours at 118°C. After the addition was completed, the temperature was maintained at 118°C for 2.9 hours. Then, 0.48 parts by weight of 2,2'-azobisisobutyronitrile was pre-dissolved in 8.0 parts by weight of n-butyl acetate to form a replenishing solution, which was then added, and the temperature was maintained for another 1.4 hours. The solution was cooled to 58°C, and partially butyl acetate was removed under reduced pressure at 58°C and 0.06 MPa. The solid content was then adjusted with butyl acetate to obtain an acrylic copolymer resin solution with a solid content of 42.5 wt%. The resulting acrylic copolymer resin had an acid value of 20 mg KOH / g and a hydroxyl value of 75 mg KOH / g. II. Preparation of silane-functionalized acrylic copolymer resin: Take the above acrylic copolymer resin solution, and add 14 parts by weight of 3-glycidyloxypropyltrimethoxysilane to 100 parts by weight of the acrylic copolymer resin solids. React at 88°C for 3.8 h under nitrogen protection. The acid value of the silane-functionalized acrylic copolymer resin obtained after the reaction is 18 mg KOH / g. Cool to 58°C, and remove part of the n-butyl acetate under reduced pressure at 58°C and 0.06 MPa. Adjust the solid content with n-butyl acetate to obtain a silane-functionalized acrylic copolymer resin solution with a solid content of 48.5 wt%. III. Preparation of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate: 15 parts by weight of silica were added to 120 parts by weight of ethanol. The silica was uniformly dispersed by ultrasonication at 22°C with a power of 320 W, a frequency of 22 kHz, and a time of 35 min. At 23°C, 12 parts by weight of deionized water were added first, followed by 0.8 parts by weight of glacial acetic acid, to adjust the apparent pH of the system to 5.8, and this pH was maintained for 0.6 h. A silane-functionalized acrylic copolymer resin solution was added to the above system, with 18 parts by weight based on the solid content of the silane-functionalized acrylic copolymer resin. The reaction was carried out at 43°C for 1.2 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. Ethanol and water were removed by rotary evaporation at 42°C and 0.03 MPa absolute pressure, with simultaneous addition of butanone and ethyl acetate to complete solvent replacement, yielding a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion with a solid content of 24.0 wt%, residual ethanol content of 0.3 wt%, and residual water content of 0.1 wt%. In this embodiment, the silica content in the core-shell intermediate was 45.5 wt% on a dry basis, the core particle size was 15 nm, the shell thickness was 4 nm, and the core and shell exhibited an interfacial bonding state with silicon-oxygen bonding characteristics. IV. Preparation of Hydroxyl-Containing Polyurethane Resin: 100 parts by weight of polytetramethylene ether glycol, 0.28 parts by weight of 1,4-butanediol, 11.66 parts by weight of isophorone diisocyanate, and 80.9 parts by weight of n-butyl acetate were provided, with a number average molecular weight of 2000 g / mol and a hydroxyl value of 56 mg KOH / g. The mixture was formulated with a molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol of 1.049. Under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol were reacted at 89°C for 2.9 h to obtain an isocyanate-terminated prepolymer. 1,4-Butanediol was added to achieve a molar ratio of hydroxyl groups provided by 1,4-butanediol to residual isocyanate groups in the isocyanate-terminated prepolymer of 1.25, and the mixture was reacted at 79°C for 3.8 h. The mixture was cooled to 58°C and adjusted with n-butyl acetate to obtain a hydroxyl-containing polyurethane resin solution with a solid content of 58.0 wt%. V. Preparation of the transparent dielectric electroplated aluminum color layer resin composition: Based on 100 parts by weight of the color layer resin composition in this embodiment, at 32°C, a silane-functionalized acrylic copolymer resin solution, a hydroxyl-containing polyurethane resin solution, and a silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion were added sequentially. After each component was added, the mixture was stirred for 19 minutes, followed by the addition of a solvent and stirring for 38 minutes. A crosslinking agent was added 1.8 hours before coating; in this embodiment, isophorone diisocyanate was used as the crosslinking agent. The mixture was stirred for 28 minutes until no visible layering or sedimentation was observed in the system.

[0045] The color layer resin composition of this embodiment comprises, by weight, the following components: 18.5 parts by weight of silane-functionalized acrylic copolymer resin, 0.8 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 9.0 parts by weight of hydroxyl-containing polyurethane resin, 0.6 parts by weight of isocyanate-containing crosslinking agent component containing isophorone diisocyanate, 9.6 parts by weight of non-volatile components in the crosslinking agent stock solution other than the isocyanate-containing crosslinking agent component, and 61.5 parts by weight of solvent. The silane-functionalized acrylic copolymer resin, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and the hydroxyl-containing polyurethane resin of this embodiment are all based on solid mass. The effective isocyanate group content of the isocyanate-containing crosslinking agent component in this embodiment is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The non-volatile components of the crosslinking agent stock solution are included in the non-volatile components of this embodiment. In this embodiment, the solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer resin is 0.043. The solvent in this embodiment consists of ethyl acetate, n-butyl acetate, and butanone, including the volatile solvents carried in the silane-functionalized acrylic copolymer resin solution, the core-shell intermediate dispersion, the hydroxyl-containing polyurethane resin solution, and the crosslinking agent stock solution, as well as additionally added solvent. The molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin in this embodiment is 0.82.

[0046] The color layer resin composition of this embodiment was filtered through a 6µm filter, and the non-volatile content was 38.5wt%. The color layer resin composition was coated onto the substrate using a slot coating method, with a dry film thickness of 4.8µm, a drying temperature of 128°C, and a drying time of 115s.

[0047] The above four embodiments provide illustrative coverage of representative formulation ranges and related application scenarios for transparent dielectric electroplated aluminum color layer resin compositions. Example 1 uses moderate formulation parameters. The monomer composition of methyl methacrylate and butyl acrylate provides a good balance between hardness and flexibility. The silica content, core particle size, and shell thickness of the core-shell intermediates are all at moderate levels, which is conducive to good dispersion of nanoparticles. The dry film thickness is moderate, making it suitable for applications with balanced comprehensive performance, such as cigarette packaging printing, anti-counterfeiting labels, and trademark decoration. Example 2 uses a lower resin ratio and a higher solvent content. The butyl acrylate content is increased to enhance flexibility. The core-shell intermediates employ a moderate silica dry basis content and a smaller particle size design to reduce light scattering. The dry film thickness is thinner, and the amount of crosslinking agent is less. This relatively low crosslinking agent metering design makes it suitable for applications with high requirements for extensibility and rapid curing, such as flexible cigarette labels and heat transfer films. Example 3 employs a higher resin ratio and solid content, with increased methyl methacrylate content to enhance hardness. The core-shell intermediate uses a medium silica dry basis content and a larger particle size to achieve nano-reinforcement, resulting in a thicker dry film. A higher dosage of crosslinking agent is used, making it suitable for high-end cigarette packaging, anti-counterfeiting labels, and trademark decorations—applications requiring high scratch resistance and mechanical strength. Example 4 employs a higher resin bulk and a lower core-shell intermediate ratio, with higher methyl methacrylate and hydroxyethyl methacrylate contents, which facilitates the formation of a system with higher hardness and higher hydroxyl content. The core-shell intermediate uses a higher silica dry basis content and a smaller particle size to reduce light scattering. The dry film thickness is close to the upper limit, and the crosslinking agent dosage is lower. It is suitable for high-transparency anti-counterfeiting films, transparent dielectric aluminum oxide layers, and transparent anti-counterfeiting decorations for cigarette packaging—applications requiring high optical performance. These four examples, through parameter gradient design, provide exemplary coverage of different performance emphases in cigarette packaging, transparent anti-counterfeiting, and trademark decoration applications across dimensions such as monomer composition, core-shell structure, resin ratio, and process conditions, demonstrating that this technical solution has a certain degree of formulation control and application adaptability.

[0048] Comparative Example 1: Basically the same as Example 1, except that 12.5 parts by weight of silane-functionalized acrylic copolymer resin was replaced with 12.5 parts by weight of acrylic copolymer resin, while other conditions remained unchanged.

[0049] Comparative Example 2: Basically the same as Example 1, except that 3.0 parts by weight of the silica-silane-functionalized acrylic copolymer resin core-shell intermediate was replaced by a physical blend dispersion prepared according to the same dry basis mass ratio of silica to silane-functionalized acrylic copolymer resin of 35:65 as in Example 1, with the same total solid mass, obtained by directly mixing silica and silane-functionalized acrylic copolymer resin. Other conditions remained unchanged.

[0050] Comparative Example 3: It is basically the same as Example 1, except that the amount of silica-silane functionalized acrylic copolymer core-shell intermediate is 0.2 parts by weight, and the remaining solvent is adjusted to make the total amount of the formulation 100 parts by weight, while other preparation conditions remain unchanged.

[0051] Comparative Example 4: Basically the same as Example 1, except that the particle size of the nucleus in the core-shell intermediate of this comparative example is 75 nm, and other conditions remain unchanged.

[0052] Comparative Example 5: It is basically the same as Example 1, except that the shell thickness in the core-shell intermediate of this comparative example is 1 nm, and other conditions remain unchanged.

[0053] Comparative Example 6: It is basically the same as Example 1, except that the molar ratio of the isocyanate group provided by the crosslinking agent to the hydroxyl group provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin is 0.60, and other conditions remain unchanged.

[0054] Comparative Example 7: It is basically the same as Example 1, except that in step S5, the crosslinking agent is added to the system immediately after the solvent is added, and then the remaining resin components are added, while other conditions remain unchanged.

[0055] Comparative Example 8: Basically the same as Example 1, except that the filtration accuracy before coating was 30µm, and other conditions remained unchanged.

[0056] Performance testing: Optical performance testing: The color layer was coated on a 50μm transparent PET substrate, and the dry film thickness was controlled at 2.8±0.2μm. After the samples were placed in an environment of 23℃ and 50%RH for 24h, five 50mm×50mm test pieces were taken from each sample. The total transmittance and the proportion of scattered light after light passed through the sample were measured using a haze meter. The average value ± standard deviation was output. The transparent appearance of the material was evaluated by the total transmittance and haze.

[0057] Pencil hardness test: After the dried paint film is placed in an environment of 23℃ and 50%RH for 24 hours, pencils of different hardness are used to scratch the film surface at a uniform speed at a 45° angle and a load of 750g. The test is performed 3 times in each of the three different directions. The highest hardness level that does not produce obvious scratches is recorded. The median value of the consistent level is taken as the result. The hardness and scratch resistance of the paint film surface are determined by linking the results with the wear resistance data.

[0058] Abrasion resistance test: The cured color coating film was subjected to a rotary abrasion test. Using a CS-10 grinding wheel, a 500g load, and 500 revolutions, the film layer was worn by friction of the grinding wheel. The mass loss after 500 revolutions was recorded. Three parallel samples were used in each group. The average weight loss ± standard deviation was output. The lower the value, the better the abrasion resistance. The actual abrasion resistance retention ability under high hardness system was evaluated.

[0059] Adhesion test: After the coated and dried color film / substrate composite sample was placed in an environment of 23℃ and 50%RH for 24 hours, a cross-cut test was performed with a cross-cut spacing of 1mm, cutting to the substrate. The sample was peeled off with tape, and the coating peeling was observed to determine the grade. Three samples were used in each group. The adhesion grade was output and analyzed in conjunction with transparency and abrasion resistance to evaluate the interfacial bonding quality and adhesion stability between the color layer and the substrate or adjacent layers.

[0060] Solvent resistance test: The fully cured color film was wiped with MEK as the wiping medium under the conditions of wiping load of 9.8N, reciprocating stroke of 100mm, wiping frequency of 60 times / min and cotton cloth of the same specification. Each reciprocating stroke was counted as 1 time until the film surface showed obvious failure phenomena such as loss of gloss, stickiness, exposure of the substrate or damage. Three parallel samples were tested in each group. The average value of the number of wiping cycles ± standard deviation was output. The optimal window was analyzed in combination with the crosslinking agent molar ratio to examine the integrity of the crosslinking network and the solvent resistance wiping stability.

[0061] Process performance testing: Before coating, the non-volatile content and apparent viscosity under specified shear conditions of the color layer resin composition were determined. The non-volatile content was determined by the isothermal drying method. After sampling, the sample was dried at 105℃ for 1 hour, and the percentage of the dried residual mass to the initial mass of the sample was taken as the non-volatile content. The apparent viscosity in Table 1 was tested by rotational viscometer at 25±0.5℃ using a No. 3 rotor and 60r / min. Each group of samples was repeated 3 times. The average value ± standard deviation of non-volatile content and viscosity were output to evaluate the matching relationship between non-volatile content, apparent viscosity, coating stability and film uniformity.

[0062] Structural characterization tests: ATR-FTIR was used to acquire spectra of silane-functionalized acrylic copolymer resin, silica-silane-functionalized acrylic copolymer resin core-shell intermediate, and final color layer dry film. The spectra ranged from 4000 to 650 cm⁻¹ with a resolution of 4 cm⁻¹. The scans were performed 32 times, and baseline correction was performed and repeated 3 times. The changes in the peak position and area ratio of Si–O–Si, Si–OH, and urethane-related absorption peaks were compared. The peak area ratio of Si–O–Si / Si–OH and the carbonyl peak position shift were output to compare the silicon-oxygen bonding characteristics of the core-shell interface and the interface coupling characteristics after curing.

[0063] To verify the reinforcing effect of the silica-silane functionalized acrylic copolymer core-shell intermediate in the transparent color layer resin system, a gradient experiment of formulation parameters was first conducted based on Example 1. Figure 1The effect of the amount of silica-silane-functionalized acrylic copolymer core-shell intermediate on transmittance and abrasion weight loss is shown in the figure. While keeping the silane-functionalized acrylic copolymer resin, hydroxyl-containing polyurethane resin, crosslinking agent, coating process, and test conditions consistent, the amount of core-shell intermediate was varied and supplemented to 100 parts by weight using solvent. The variables were set as 0.2, 0.5, 1.5, 3.0, 4.5, 6.0, and 7.2 parts by weight. The results show that when the amount of core-shell intermediate is low, the coating's abrasion resistance enhancement effect is insufficient, and the abrasion weight loss is high; when the amount is too high, the inorganic phase content in the system increases, the interparticle interaction is enhanced, which easily leads to an increase in microscopic scattering centers and a decrease in transmittance. When the amount of core-shell intermediate is 3.0 parts by weight, the light transmittance of the coating is about 92.6% and the wear resistance weight loss is about 18 mg / 500 r. This indicates that an appropriate amount of core-shell intermediate can achieve a better balance between transparency and wear resistance, providing experimental evidence for solving the problem that the addition of reinforcing fillers in transparent color layers easily sacrifices the transparent appearance.

[0064] Based on determining the appropriate dosage of the core-shell reinforcing component, the influence of the degree of cross-linking curing on the overall performance of the coating was further investigated. Figure 2 The graph shows the effect of the isocyanate to hydroxyl molar ratio on transmittance and abrasion weight loss. Using Example 1 as a baseline, only the isocyanate to hydroxyl molar ratio was varied, with variables set to 0.60, 0.80, 0.90, 1.00, 1.10, 1.20, and 1.35. The results show that when the isocyanate to hydroxyl molar ratio is low, the system has insufficient crosslinking, the coating network structure is not dense enough, and the abrasion weight loss is relatively high. When the molar ratio is too high, excessive crosslinking agent may lead to localized hardening and embrittlement or uneven microphase structure, adversely affecting transparency and film continuity. When the isocyanate to hydroxyl molar ratio is around 1.00, the transmittance is approximately 92.6%, and the abrasion weight loss is approximately 18 mg / 500 r, indicating that an appropriate degree of crosslinking reaction can match the resin's continuous film-forming ability and network curing ability, thereby improving the abrasion resistance, structural integrity, and optical stability of the transparent color layer.

[0065] To further clarify the influence of core-shell particle structure parameters on the transparency enhancement effect, the silica core particle size and organic shell thickness were adjusted respectively. Figure 3The graph shows the effect of silica core particle size on transmittance and wear resistance weight loss. Using Example 1 as a baseline, only the core particle size was varied, with variables set to 8, 10, 22, 35, 52, 60, and 75 nm. The results show that when the core particle size is too small, the particle surface energy is high, limiting the stability of the dispersion system and the reinforcing efficiency. When the core particle size is too large, the relative matching relationship between the particles and the visible light wavelength scale changes, increasing the risk of light scattering and potentially weakening the transparent appearance of the transparent dielectric layer. When the silica core particle size is 35 nm, the coating transmittance is approximately 92.6%, and the wear resistance weight loss is approximately 18 mg / 500 r, indicating that a moderate particle size can provide effective inorganic hardening reinforcement while reducing the adverse effects of particles on the transparent appearance. Figure 4 The graph shows the effect of shell thickness on transmittance and wear resistance weight loss, using Example 1 as a baseline, with only the shell thickness varied. The variables were set to 1, 3, 6, 9, 12, 15, and 18 nm. The results show that when the shell is too thin, the compatibility between the inorganic silica surface and the resin matrix is ​​insufficiently improved, easily leading to local agglomeration or interface defects. When the shell is too thick, the proportion of the organic coating layer increases, the reinforcing efficiency of the hard core decreases, and it may also affect the system's flow and curing uniformity. When the shell thickness is 9 nm, the coating transmittance is approximately 92.6%, and the wear resistance weight loss is approximately 18 mg / 500 r, indicating that the approximately 53 nm core-shell particle structure formed by a 35 nm core particle size and a 9 nm shell thickness can effectively balance dispersion stability, interfacial bonding, and wear resistance enhancement.

[0066] After optimizing the formulation structure parameters, the influence of drying conditions during the continuous film formation process on the coating performance was further investigated. Figure 5 The graph shows the effect of drying temperature on light transmittance and abrasion weight loss. Using Example 1 as a baseline, only the drying temperature was varied, with variables set at 50, 60, 75, 95, 115, 130, and 145°C. The results show that when the drying temperature is too low, solvent evaporation and curing reactions are insufficient, resulting in inadequate coating density and abrasion resistance. When the drying temperature is too high, rapid solvent escape and accelerated local curing may lead to increased internal stress in the film, increased micro-roughness, or the formation of local defects. When the drying temperature is 95°C, the coating transmittance is approximately 92.6%, and the abrasion weight loss is approximately 18 mg / 500 r, indicating that this drying temperature is conducive to the coordinated release of solvent, resin leveling, and cross-linking curing processes, thereby forming a uniform and dense transparent color layer. Figures 1 to 5 It can be seen that the amount of core-shell intermediate, crosslinking molar ratio, core particle size, shell thickness and drying temperature are not isolated influences, but jointly determine the comprehensive balance of transparent film formation, interface enhancement, transparent appearance and wear resistance and durability.

[0067] To further explain the reasons for the above performance improvement from the perspective of chemical structure, the characteristic bonding states of the examples and comparative examples were analyzed. Figure 6The ATR-FTIR normalized spectra of Example 1, Comparative Example 1, and Comparative Example 2 are shown, comparing the changes in characteristic absorption peaks such as Si–O–Si, Si–OH, and urethane. In Example 1, the characteristic peak of Si–O–Si is relatively enhanced, while the residual signal of Si–OH decreases. This change is consistent with the high degree of silane-oxygen condensation and interfacial bonding between the silane-functionalized acrylic copolymer resin and the silica surface. Simultaneously, the urethane structure formed by the hydroxyl-containing polyurethane resin and the crosslinking agent contributes to the construction of a continuous organic network. These results indicate that the performance improvement of Example 1 is related to the synergistic effect between the organic phase, inorganic phase, and crosslinking network.

[0068] Figure 7 This is an example of XPS Si 2p peak fitting from Example 1, including the Si–O–Si peak, Si–OH peak, background line, overall fitting curve, and residual curve. The peak fitting results show that the Si–O–Si peak accounts for a relatively high proportion in Example 1, indicating that silicon mainly exists in a relatively stable silicon-oxygen linked form, with a low proportion of unreacted silanol groups. This result is consistent with... Figure 6 The infrared analysis corroborates each other, further indicating that the surface of the core-shell intermediate has a high proportion of silicon-oxygen bonding environment, consistent with the characteristics of inorganic-organic interface bonding. Figure 8 The chart shows the peak area ratios of Si–O–Si / Si–OH for Examples 1, 1 Comparative Example, and 2. The peak area ratio for Example 1 is approximately 2.85, while for Comparative Example 1 and 2 it is approximately 1.18 and 1.35, respectively. The significantly higher peak area ratio in Example 1 indicates a higher degree of silicon-oxygen condensation, providing structural characterization evidence for its wear resistance, solvent resistance, and transparent appearance.

[0069] Based on the analysis of interfacial bonding characteristics, the structural controllability of core-shell particles at the nanoscale is further characterized by particle size distribution. Figure 9 The figures show the TEM particle size distribution curves for Examples 1, 2, and 4. In Example 1, the silica core particle size is mainly concentrated around 35 nm, with a narrow particle size distribution. In Comparative Example 2, the apparent particle size distribution of silica particles or agglomerates is wider, indicating poor particle size uniformity and dispersion uniformity in the physical blend system. In Comparative Example 4, the particle size is relatively large and concentrated around 75 nm, which easily increases the risk of light scattering and local filler enrichment. These results indicate that Example 1, by pre-constructing a core-shell intermediate, allows the inorganic hard core to participate in the film formation and curing process at a more uniform scale, which is beneficial for improving wear resistance while reducing adverse effects on transparency and transparent appearance.

[0070] To evaluate the integrity of the crosslinked network and its contribution to the coating durability, the gel content, swelling ratio, solvent wiping resistance, and abrasion weight loss were further compared. Figure 10The graph shows the gel content of Example 1, Comparative Example 6, and Comparative Example 7. The gel content of Example 1 is about 86.5%, which is higher than that of Comparative Example 6 (63.8%) and Comparative Example 7 (76.5%). This indicates that the cross-linking reaction in Example 1 is more complete, resulting in a higher proportion of insoluble network structure. Figure 11 The graph shows the swelling ratios of Examples 1, 6, and 7. The swelling ratio of Example 1 is approximately 1.22, lower than that of Comparative Example 6 (1.72) and Comparative Example 7 (1.48). This indicates that the network structure of Example 1 is more dense, effectively limiting the entry of solvent molecules into the coating and demonstrating better dimensional stability and resistance to media penetration. The increase in gel content corresponds to the decrease in swelling ratio, indicating a good synergistic relationship between the curing effect of the crosslinking agent, the film-forming regulating effect of the hydroxyl-containing polyurethane resin, and the interfacial strengthening effect of the core-shell intermediate in this system.

[0071] Figure 12 The graph shows the MEK abrasion resistance statistics for Examples 1, 6, and 7. Example 1's MEK abrasion resistance is approximately 168 cycles, higher than the 88 cycles for Comparative Example 6 and 146 cycles for Comparative Example 7. This result further demonstrates that the coating of Example 1 can maintain good film integrity under the action of organic solvents and is not prone to softening, swelling, or surface damage. Figure 13 The chart shows the abrasion weight loss statistics for Example 1, Comparative Example 6, and Comparative Example 7. The abrasion weight loss of Example 1 is approximately 18 mg / 500 r, lower than that of Comparative Example 6 (31 mg / 500 r) and Comparative Example 7 (25 mg / 500 r). Combined with... Figures 10 to 13 It can be seen that the improved wear resistance of Example 1 is consistent with the combined effects of core-shell particle reinforcement, continuous resin phase film formation, and cross-linked network curing. Furthermore, based on the transmittance and haze data in Table 1, it can be seen that this improvement did not lead to a significant deterioration in the transparent appearance.

[0072] In addition to the properties of the cured film, the rheological behavior and storage dispersion stability of the color layer resin composition before coating also directly affect the continuous film formation effect. Figure 14 The viscosity-shear rate rheological curves for Example 1 and Comparative Example 7 are shown, with the tested shear rate range being 0.1–100 s⁻¹. The apparent viscosity of Example 1 decreased from approximately 690 mPa·s to approximately 305 mPa·s, and the apparent viscosity of Comparative Example 7 decreased from approximately 930 mPa·s to approximately 620 mPa·s. Figure 14 The viscosity-shear rate data are rheological scanning data, and the apparent viscosity in Table 1 is the rotational viscometer test data under constant rotation speed conditions. Example 1 has moderate viscosity under low shear conditions, which is beneficial for suppressing particle sedimentation; under high shear conditions, the viscosity decreases significantly, which is beneficial for transfer, spreading, and leveling during the gravure coating process. In contrast, Comparative Example 7 has an overall higher viscosity, insufficient fluidity under high shear, and easily affects the uniformity of film coating. Figure 15The graphs show the settling height curves for static stability of Example 1 and Comparative Example 7, with a test time of 0–48 hours. In Example 1, the settling height ratio was approximately 2.0% after 48 hours, while in Comparative Example 7 it was approximately 12.0%. This indicates that the system prepared using the mixing sequence described in Example 1 is less prone to significant settling and stratification during static standing, thus contributing to maintaining consistency in liquid preparation and stability of the final coating during production.

[0073] Based on the improved dispersion stability and rheological adaptability, the optical performance of the final transparent color layer is further evaluated. Figure 16 The chart shows the transmittance statistics for Example 1, Comparative Example 7, and Comparative Example 8. The transmittance of Example 1 is approximately 92.6%, higher than the 90.2% of Comparative Example 7 and 91.1% of Comparative Example 8. This result indicates that, based on the core-shell particle structure, employing an appropriate mixing sequence and filtration precision is beneficial for maintaining high transmittance. The combination of a 35nm core particle size, a 9nm shell thickness, an approximately 53nm core-shell particle outer diameter, and an appropriate cross-linking structure effectively reduces light scattering caused by particle agglomeration, interface discontinuities, and film roughness. Therefore, this solution not only improves the coating's wear resistance and solvent resistance but also maintains the high transparency required for the transparent dielectric electroplated aluminum color layer, providing a stable optical foundation for the transparent dielectric electroplated aluminum color layer.

[0074] To verify the aforementioned optical and dispersion properties from a macroscopic film-forming effect, Figure 17 The images show macroscopic optical photographs comparing the final product of Example 1 and the final product of Comparative Example 2, used to compare the overall appearance, continuity, and uniformity of the transparent dielectric electroplated aluminum color layer resin dry film. Figure 17 Image a shows a macroscopic optical photograph of the final product of Example 1. The sample is a transparent dielectric electroplated aluminum color layer resin dry film obtained by 12µm filtration, gravure coating, and drying at 95℃ for 65s. The dry film thickness is 2.8µm, with a silica core particle size of 35nm and a silane-functionalized acrylic copolymer resin shell layer thickness of 9nm. The outer diameter of the core and shell particles is approximately 53nm. As can be seen from the figure, the color layer of Example 1 is continuous, transparent, and uniform in appearance, consistent with the results showing good dispersion and film stability of the core-shell intermediate during continuous coating and drying. Figure 17 b is a macroscopic optical photograph of the final product of Comparative Example 2. This sample used a physical blend dispersion of silica and silane-functionalized acrylic copolymer resin to replace the core-shell intermediate, and other film-forming conditions were the same as in Example 1. In Comparative Example 2, due to the lack of a pre-constructed core-shell interface, the compatibility between the particles and the resin was insufficient, which easily led to a decrease in the uniformity of the coating appearance and the dispersion stability. Figure 17 The comparison results, from a macroscopic perspective, demonstrate that the core-shell structure design can improve the continuous film quality of the transparent color layer and reduce common problems in physical blending systems such as particle enrichment, film surface unevenness, and insufficient optical stability.

[0075] To further verify the dispersion advantages of core-shell intermediates from the perspectives of surface morphology and film structure, Figure 18 The image shows a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 2. Figure 18 Image a is a low-magnification SEM image of the final product of Example 1, showing the large-area surface morphology of the 2.8µm color layer dry film. The coating is continuous overall, and no obvious coarse defects are observed, indicating that the formulation system of Example 1 is suitable for forming a uniform and transparent film structure. Figure 18 b is a low-magnification SEM image of the final product of Comparative Example 2, showing the surface morphology of the color layer formed by the physically blended silica system. It can be used to illustrate that local particle enrichment or uneven coating is more likely to occur when the core-shell interface is not pre-constructed. Figure 18 c is a magnified SEM image of the final product of Example 1, showing the local area or cross-sectional structure of the dry film, indicating that the 2.8µm film layer has good continuity and interface integrity; Figure 18 Image d is a magnified SEM image of the final product of Comparative Example 2, showing the local coating structure of the physical blend system. It can be seen that its local uniformity is relatively insufficient, indicating that insufficient interfacial compatibility between silica and resin may cause local defects. Figure 18 e is a high-magnification SEM image of the final product of Example 1, showing the details of the coating surface and the microstructure related to the nanofiller. The core-shell particles exhibit a good dispersion state in the resin network. Figure 18 f is a high-magnification SEM image of the final product of Comparative Example 2, showing the local aggregation and surface roughness characteristics of physically blended silica in the coating. Figure 18 a to Figure 18 As can be seen from the progressively magnified observation of f, Example 1 reduced the risk of inorganic particles agglomeration in the transparent resin color layer through the core-shell treatment, thereby improving the continuity of the large-area film, the integrity of the local structure, and the uniformity of surface details.

[0076] Based on SEM observations Figure 19 The TEM structure comparison diagrams of the final product of Example 1 and the final product of Comparative Example 2 are used to further compare the interface structure and dispersion state of the silica-silane functionalized acrylic copolymer core-shell intermediate at the nanoscale. Figure 19 Image a is a bright-field TEM image of the final product of Example 1. The sample is an ultrathin local area of ​​the final color layer dry film. A 35nm silica core, a 9nm organic shell, and a core-shell particle outline of about 53nm can be observed, indicating that a clear core-shell composite structure was formed in Example 1. Figure 19 b is a bright-field TEM image of the final product of Comparative Example 2. The sample is an ultrathin local area of ​​the final dry film of the physical blend system, which can be used to illustrate that when the preset core-shell interface is not formed, silica particles are more likely to exist in a physical contact or local agglomeration state. Figure 19c is an HRTEM image of the final product of Example 1, showing the local interface of the core-shell particles and the contact state between the organic and inorganic phases, which is consistent with a relatively stable interface binding state. Figure 19 Image d is an HRTEM image of the final product of Comparative Example 2, showing a local interface between the physically blended silica and resin, whose interface continuity is weaker than that of Example 1. Figure 19 It can be seen that the core-shell particles in Example 1 are not simply physically filled into the resin matrix, but achieve stable dispersion and structural synergy at the nanoscale through interfacial coupling between the silica core, the silane-functionalized acrylic copolymer resin shell and the crosslinking network.

[0077] In conclusion, Figures 1 to 5 The optimal matching relationships between the amount of core-shell intermediates, the molar ratio of isocyanate groups to hydroxyl groups, the silica core particle size, the shell thickness, and the drying temperature were determined from the perspective of formulation and process parameters. Figures 6 to 9 The controllability of silicon-oxygen network, core-shell interface and particle size was demonstrated from the aspects of interfacial silicon-oxygen bonding characteristics, core-shell interface morphology and nanoparticle size distribution. Figures 10 to 13 The contributions of cross-linked networks and core-shell reinforced structures to the durability of the membrane were demonstrated by measuring gel content, swelling ratio, solvent wiping resistance, and abrasion weight loss. Figures 14 to 16 The rheological properties, storage stability, and light transmittance demonstrate that this resin composition is suitable for continuous coating and can maintain high transparency. Figures 17 to 19 The macroscopic appearance, SEM morphology, and TEM nanostructure further demonstrate that Example 1 exhibits better dispersion uniformity, film continuity, and interface stability. These results corroborate each other, indicating that this approach can achieve a synergistic improvement in high wear resistance, high transparency, stable dispersion, and uniform film formation within the same transparent color layer system. This effectively addresses the difficulty in simultaneously achieving enhanced performance, transparent appearance, and film uniformity in existing transparent dielectric electroplated aluminum color layer systems.

[0078]

[0079] As can be seen from the performance of the examples and comparative examples in Table 1, the overall system of the examples achieves a better balance between high transparency, low haze, abrasion resistance, adhesion, and solvent resistance. Among them, Example 1 has the most balanced overall performance, Example 2 is biased towards ultra-thin flexibility and optical transparency, Example 3 is biased towards high hardness and abrasion resistance, and Example 4 is biased towards high solids content and high transparency. In contrast, removing the silane functionalized structure, changing the core-shell intermediate to physical blending, deviating from the core particle size or shell thickness window, and deviating from the crosslinking metering and timing will all lead to weakened interfacial coupling, enhanced scattering, incomplete curing network, or decreased construction stability, thereby causing a synergistic deterioration of key indicators such as transmittance, haze, abrasion resistance, and solvent resistance.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A transparent dielectric electroplated aluminum color layer resin composition, characterized in that, The total weight of the components in the color layer resin composition is 100 parts by weight, comprising: 5.0 to 20.0 parts by weight of silane-functionalized acrylic copolymer resin, 0.5 to 6.0 parts by weight of silica-silane-functionalized acrylic copolymer resin core-shell intermediate, 1.0 to 10.0 parts by weight of hydroxyl-containing polyurethane resin, 0.7 to 16.0 parts by weight of non-volatile components of the crosslinking agent stock solution, including 0.2 to 4.0 parts by weight of crosslinking agent component containing isocyanate groups and 0.5 to 12.0 parts by weight of non-volatile components other than the crosslinking agent component containing isocyanate groups, and the balance being solvent; the silane-functionalized acrylic copolymer resin, the silica... The core-shell intermediate of the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin are both based on solid mass. The non-volatile components of the crosslinking agent stock solution are based on the residual mass after drying at 105°C for 1 hour. The effective isocyanate group content of the crosslinking agent component containing isocyanate groups is used to calculate the molar ratio of isocyanate groups to hydroxyl groups. The volatile solvents carried in the crosslinking agent stock solution are included in the balance solvent. The core of the core-shell intermediate is silicon dioxide, and the shell is the silane-functionalized acrylic copolymer resin. The molar ratio of the isocyanate groups provided by the crosslinking agent to the hydroxyl groups provided by the silane-functionalized acrylic copolymer resin and the hydroxyl-containing polyurethane resin is 0.80 to 1.

20.

2. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The crosslinking agent component containing isocyanate groups is selected from one or both of hexamethylene diisocyanate trimer and isophorone diisocyanate; the solvent is selected from one or more of acetone, butanone, ethyl acetate, n-propyl acetate and n-butyl acetate; the silane-functionalized acrylic copolymer resin is obtained by reacting an acrylic copolymer resin composed of methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and acrylic acid with 3-glycidoxypropyltrimethoxysilane.

3. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The acrylic copolymer resin is prepared according to the following steps: A1. A monomer mixture is prepared based on a total monomer mass of 100 parts by weight, wherein the monomer mixture consists of 35-55 parts by weight of methyl methacrylate, 25-45 parts by weight of butyl acrylate, 12-18 parts by weight of hydroxyethyl methacrylate and 3-8 parts by weight of acrylic acid, and the total is 100 parts by weight. A2, add 120-260 parts by weight of n-butyl acetate to the reaction vessel, and heat to 100-120°C under nitrogen protection; A3, dissolve 0.3 to 1.5 parts by weight of 2,2'-azobisisobutyronitrile in 10 to 40 parts by weight of n-butyl acetate to obtain an initiator solution, and simultaneously add the monomer mixture and the initiator solution dropwise over 2.0 to 4.0 hours at 100 to 120°C; A4. After the addition is complete, keep the temperature at 100-120℃ for 2.0-3.0h, then add 0.05-0.50 parts by weight of 2,2'-azobisisobutyronitrile. The added 2,2'-azobisisobutyronitrile is pre-dissolved in 1-10 parts by weight of n-butyl acetate to form a replenishing solution before being added to the reaction system, and the temperature is kept high for another 0.5-1.5h. A5, cooled to 40-60℃, and according to the solid content test results, under reduced pressure at 40-60℃ and an absolute pressure of 0.04-0.06MPa, some of the n-butyl acetate was removed or n-butyl acetate was added to adjust the solid content, to obtain the acrylic copolymer resin solution with a solid content of 25.0-43.0wt%. A6, the resulting acrylic copolymer resin has an acid value of 15-35 mg KOH / g and a hydroxyl value of 50-77 mg KOH / g based on resin solids.

4. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The silane-functionalized acrylic copolymer resin was prepared according to the following steps: B1, take an acrylic copolymer resin solution, and add 1 to 15 parts by weight of 3-glycidyloxypropyltrimethoxysilane to 100 parts by weight of the acrylic copolymer resin solids. B2, under nitrogen protection, reacts at 60–90°C for 1.0–4.0 h; B3, the acid value of the silane-functionalized acrylic copolymer resin obtained after the reaction is 5-35 mg KOH / g based on resin solids; B4 is cooled to 40–60°C. Based on the solid content test results, some of the n-butyl acetate is removed under reduced pressure at 40–60°C and an absolute pressure of 0.04–0.06 MPa, or n-butyl acetate is added to adjust the solid content, to obtain the silane-functionalized acrylic copolymer resin solution with a solid content of 25.0–50.0 wt%.

5. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The silica-silane-functionalized acrylic copolymer core-shell intermediate was prepared according to the following steps: C1, add 10 to 60 parts by weight of silica to 100 to 400 parts by weight of ethanol to form a silica dispersion system without visible agglomerates; C2, add 5-80 parts by weight of deionized water and 0.1-10 parts by weight of glacial acetic acid at 20-40℃ to make the apparent pH of the system 4.0-6.0 and maintain it for 0.5-2.0h; C3. Add a silane-functionalized acrylic copolymer resin solution to the system obtained in step C2, with 10 to 120 parts by weight of the silane-functionalized acrylic copolymer resin solids, and react at 40 to 70°C for 1.0 to 4.0 h to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion system. C4, at 40–60°C and an absolute pressure of 0.02–0.08 MPa, the ethanol and water in the core-shell intermediate dispersion system obtained in step C3 are replaced with one or more of acetone, butanone, ethyl acetate, n-propyl acetate, and n-butyl acetate to obtain the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, wherein the residual ethanol content after solvent replacement is not higher than 1.0 wt%, and the residual water content is not higher than 0.5 wt%. C5, wherein the silica content in the core-shell intermediate is 10-60 wt% based on the total dry basis of the core-shell intermediate, the core particle size is 10-60 nm, and the shell thickness is 3-15 nm.

6. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The hydroxyl-containing polyurethane resin is prepared according to the following steps: D1, based on 100 parts by weight of polytetramethylene ether glycol, provides polytetramethylene ether glycol with a number average molecular weight of 1800-2200 g / mol and a hydroxyl value of 50-65 mg KOH / g, 0.05-0.50 parts by weight of 1,4-butanediol, 10.0-13.0 parts by weight of isophorone diisocyanate and 70-255 parts by weight of n-butyl acetate; D2 is prepared with the molar ratio of isocyanate groups to hydroxyl groups provided by polytetramethylene ether glycol being 1.02 to 1.

05. D3, under nitrogen protection, isophorone diisocyanate and polytetramethylene ether glycol are reacted at 70-90°C for 1.0-3.0 h to obtain isocyanate-terminated prepolymer; D4, add 1,4-butanediol, and based on the residual isocyanate group content at the end of step D3, make the molar ratio of the hydroxyl groups provided by 1,4-butanediol to the residual isocyanate groups 1.05 to 1.30, and react at 60 to 80°C for 1.0 to 4.0 h. D5, cooled to 40-60°C, and butyl acetate was added to adjust the solid content according to the solid content test results, to obtain the hydroxyl-containing polyurethane resin solution with a solid content of 30.0-60.0 wt%.

7. The transparent dielectric electroplated aluminum color layer resin composition as described in claim 1, characterized in that, The solid mass ratio of the silica-silane-functionalized acrylic copolymer core-shell intermediate to the silane-functionalized acrylic copolymer is 1:40 to 6:5; the crosslinking agent component containing isocyanate groups is hexamethylene diisocyanate trimer, and the amount of the crosslinking agent component containing isocyanate groups is 0.5 to 3.0 parts by weight; the solvent is composed of ethyl acetate and n-butyl acetate, or composed of ethyl acetate, n-butyl acetate, and one or more selected from acetone, butanone, and n-propyl acetate, and the sum of the amounts of each solvent component relative to the total amount of the color layer resin composition is the balance solvent in the color layer resin composition.

8. A method for preparing a transparent dielectric electroplated aluminum color layer resin composition as described in any one of claims 1-7, characterized in that, Includes the following steps: S1 provides an acrylic copolymer resin solution; S2, react the acrylic copolymer resin solution provided in step S1 with 3-glycidyloxypropyltrimethoxysilane to obtain a silane-functionalized acrylic copolymer resin solution. S3 provides a silica-silane-functionalized acrylic copolymer core-shell intermediate dispersion; S4 provides a hydroxyl-containing polyurethane resin solution; S5, at 15-35°C, the silane-functionalized acrylic copolymer resin solution provided in step S2, the hydroxyl-containing polyurethane resin solution provided in step S4, the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion provided in step S3, and the solvent are mixed and stirred in sequence, and then a crosslinking agent is added to obtain the transparent dielectric electroplated aluminum color layer resin composition.

9. The method as described in claim 8, characterized in that, The crosslinking agent in step S5 is added 0.1 to 2.0 hours before coating; the color layer resin composition obtained in step S5 is filtered through a filter medium with a rated filtration accuracy of 5 to 20 µm before coating, and the non-volatile content of the color layer resin composition is 20.0 to 40.0 wt%; the color layer resin composition obtained in step S5 is further coated using one of gravure coating, microgravure coating, or slot coating; the resulting dry film thickness is 0.5 to 5.0 µm; the drying temperature is 60 to 130 °C, and the drying time is 10 to 120 s.

10. The method as described in claim 8, characterized in that, The preparation processes of the acrylic copolymer resin solution provided in step S1, the silane-functionalized acrylic copolymer resin solution provided in step S2, and the hydroxyl-containing polyurethane resin solution provided in step S4 are all carried out under nitrogen protection. In step S5, after adding the silane-functionalized acrylic copolymer resin solution and the hydroxyl-containing polyurethane resin solution, they are stirred for 10-20 min respectively. After adding the silica-silane-functionalized acrylic copolymer resin core-shell intermediate dispersion, they are stirred for 10-20 min. After adding the solvent, they are stirred for 20-40 min. After adding the crosslinking agent, they are stirred for 10-30 min.

Citation Information

Patent Citations

  • Production process of transparent holographic film with high refractive index

    CN104029512A

  • Coloring agent for electrochemical aluminum paint and its preparing method

    CN1944552A